The Role of Solid Fuel Production in the Concentration of Brick Manufacturing Industries in Ouled Settout, Nador Province (NE Morocco) - El Monhim Bilal; Hlal Mohammed; Arabi Mourad; Mechkirrou Latifa; Elouassidi Abdelhafid; Sbai Abdelkader; Makkaoui Mohamed; Benrbia Khadija (E3S Web of Conferences)
This study examines the spatial implications of energy infrastructure on industrial development in northeastern Morocco, with a particular focus on the relationship between the proximity to a petcoke- based energy facility—located in the Ouled Settout municipality of Nador Province—and key industrial performance indicators, namely production output, workforce size, and the total surface area of industrial establishments. Employing a descriptive-analytical methodology, the research integrates both administrative datasets and qualitative field interviews conducted with representatives of 21 industrial units, selected as the study sample. A combination of statistical techniques was applied to evaluate the significance and strength of the observed correlations. The findings reveal a statistically significant association (p < 0.05) between distance from the petcoke facility and the industrial variables under consideration. ENERGIE GM MAROC, the energy operator in question, imports petcoke through the Port of Nador and has experienced marked growth in production volumes between 2010 and 2021. This expansion has contributed to a spatial concentration of 19 red brick manufacturing units and two cement plants within the surrounding area. Notably, the results indicate that red brick factories exhibit a higher tendency to locate near the petcoke source compared to cement plants, suggesting sector-specific spatial behaviors in response to energy availability and cost-efficiency considerations.